Healthcare workers and measles outbreaks in Italy: is it time to act? A systematic review. (13th November 2019) - Baccolini, V; Sindoni, A; Adamo, G; Rosso, A; Massimi, A; Pitini, E; De Vito, C; Marzuillo, C; Villari, P
Abstract: Background: Despite healthcare workers (HCWs) vaccination against measles is strongly recommended in Europe, many studies showed their low vaccination coverage and a significant involvement in hospital and community outbreaks. The aim of this systematic review was to analyze the available evidence on HCW role in measles outbreaks and identify the epidemiological characteristics of the transmission patterns related to HCW infection. Methods: PubMed, Scopus and ISI Web of Science were searched to detect the measles outbreaks occurred in Italy and involving at least one HCW. English or Italian records were considered eligible. The quality assessment was performed using the ORION checklist. We also analyzed national or regional measles reports and the Measles outbreaks reporting forms that are annually submitted to the World Health Organization (WHO) of the period 2014-2018. Results: Twenty-one articles were identified in the literature search and were in general of good quality. Of these, six were regional or Italian reports, two referred to one city, 13 were single outbreak reports. The national data showed that the number of infected HCWs increases with the rise of the total number of cases. A total of 72 descriptions of measles outbreaks were retrieved from the WHO reports. The vast majority was confined to the hospital or started at the hospital and spread in the community. The index cases were mainly patients seeking care for measles-related symptoms but, in the last years, a growing number of infected HCWs was identified as infection source. Similarly, the number of outbreaks with more than one infected HCW recorded a small increase over time. Conclusions: HCWs play a critical role in measles transmission especially in hospital outbreaks, which are significantly costly and disruptive for the healthcare delivery quality and safety. Vaccination policy aiming at increasing their immunization rate is crucial to limit the virus spread and the economic impact on the institutions. Key messages: In spite of the remarkable progress, measles elimination in Italy is far from being met and the virus transmission in healthcare settings is increasingly notified. Vaccination policies aiming at increasing HCW immunization coverages are essential.